"Dancing on the edge of research" – What is needed to build and sustain research capacity within the massage therapy profession? A formative evaluation. Issue 2 (April 2017) - Kania-Richmond, Ania; Menard, Martha B.; Barberree, Beth; Mohring, Marvin
Summary: Background: Conducting research on massage therapy (MT) continues to be a significant challenge. Purpose: To explore and identify the structures, processes, and resources required to enable viable, sustainable and high quality MT research activities in the Canadian context. Participants: Academically-based researchers and MT professionals involved in research. Research design: Formative evaluation and a descriptive qualitative approach were applied. Results: Five main themes regarding the requirements of a productive and sustainable MT research infrastructure in Canada were identified: 1) core components, 2) variable components, 3) varying perspectives of stakeholder groups, 4) barriers to creating research infrastructure, and 5) negative metaphors. In addition, participants offered a number of recommendations on how to develop such an infrastructure. Conclusions: While barriers exist that require attention, participants' insights suggest there are various pathways through which a productive and sustainable MT research infrastructure can be achieved.